The Implementation of Wraparound Model in Israel - An Alternative to Out-of-Home Placement of Delinquent Juveniles - Elisha, Ety; Braver, Efi; Rappapor, Varda; Samuel, Tali (International Journal of Criminology and Sociology, 2022)
Wraparound model refers to community-based programs designed to rehabilitate youth; characterized by multiple risk factors, through "wrapping" them with a variety of assistance agencies, first and foremost their families. The purpose of the current paper was to describe the way of implementation of the Wraparound model in Israel, named the Ma'atefet1, which is operated by the Juvenile Probation Service (JPS), as an alternative to out-of-home placement of convicted juvenile offenders. The paper presents an overview of the program's background, objectives and goals, as well as findings of evaluation studies designed to examine the program effectiveness, and case studies of convicted minors that participated in the program in Israel. In consistent with previous studies from different countries in the world, it was found that the program in Israel achieves its main goals, reflected in improvements in the educational, familial and mental condition of the treated youth; reducing recidivism; and preventing out-of-home placement. In light of these many advantages, we recommend policy-makers to expand the program, for the benefit of young offenders, their families and the community as a whole.